UJI KUALITAS BRIKET ARANG DARI SEKAM PADI DAN SERBUK KAYU SEBAGAI BAHAN BAKAR ALTERNATIF - Urwatul Wusko, Ikna; Noraidi Maulana , Antan; Sabitah, A’yan; Misbachudin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The availability of sawdust and rice husks is abundant, so the utilization of these wastes in the South Kalimantan region is very profitable. Apart from that, there are several references that mention rice husk waste and wood dust as prospective biomass sources. In this research, the process of testing the characteristics of composite briquettes made from rice husks and wood dust as an alternative energy source was carried out. This research aims to compare the results of briquette characteristic tests with the results of previous research. The ratio of rice husk-wood dust mixture is 100:0, 70:30, 30:70, and 0:100. For each type of sample, cassava flour with a composition of 10% was used as an adhesive. Of the five parameters; water content, ash content, volatile matter content, fixed carbon, and heating value. There are two parameters that do not meet SNI standards, namely the levels of volatile substances and fixed carbon. For volatile matter levels, the value is still high, namely 45.55%, which should be ≤ 15%, while the value for carbon remains low, namely 35.56%, which should be ≥77%.